Dynamics of the bird community in the coastal environments of Ilha do Cardoso, São Paulo State, Brazil - Barbieri, Edison (2024)
This study examines the dynamics of the bird community in the coastal environments of Ilha do Cardoso, SP, considering environmental, seasonal, and geographical variables. The relevance of beach zones as unique ecosystems, where birds play fundamental roles, is highlighted. By filling gaps in local avifauna research, it provides a comprehensive view of the bird community and its seasonal variations on beaches, contributing to the understanding and conservation of these ecosystems. The study describes various bird species present, emphasizing seasonal migrations and complex ecological interactions, enriching the ecological complexity of the environment. The importance of Ilha do Cardoso’s beaches for bird reproduction, feeding, and migration is emphasized, as well as the physiological and behavioral adaptations of these birds to environmental challenges. It is concluded by highlighting the remarkable diversity of species on the island, influenced by factors such as climate and migratory events, and emphasizing the importance of behavioral and evolutionary plasticity of beach birds in the face of environmental changes.